The Retief Massacre of 6 February 1838 revisited (Historia, 2021)
This article represents an attempt to reconstruct a startling incident in the history of South Africa and to establish its significance. It searches for the answers to three related questions. What happened on that fateful morning of 6 February 1838 when the Voortrekker leader Piet Retief and his companions were overwhelmed at Mgungundlovu, the stronghold of the Zulu king Dingane? Why did the Zulu king order his warriors to kill Retief and his men; and what is the historical significance of this event? No reconstruction of any historical event is a simple undertaking. In this case the challenge for the historian is to establish, on the basis of a rather restricted pool of inconclusive evidence of which the trustworthiness is questionable, how and why Retief and his men were killed. It is never easy to establish beyond reasonable doubt why national leaders make specific decisions.
Keywords: The Retief; Massacre; February; 1838; history; South Africa; Voortrekker leader; Mgungundlovu